Pengembangan Ekowisata Taman Nasional Siberut di Kepulauan Mentawai - I Wayan Thariqy Kawakibi Pristiwasa (Universitas Merdeka Malang, 2018)
This study aims to determine the components in the development of ecotourism of Siberut national park in the Mentawai Islands is a strategic plan that can be developed for ecotourism development and aims to improve the welfare of the community. This research uses descriptive qualitative method with reference to the concept of ecotourism development. The population in this research is in the form of social situation with the participants in it are government, stakeholder, tourists and community. Instrument in this research is observation, and interview use model of coding, interpretation and congrulation. The results of this study indicate that the development ecotourism of national parks in the Mentawai islands can be seen in the aspects of nature conservation flora fauna, socio-cultural empowerment of local communities economy as well aspects of learning and education directly to the government, stakeholder, tourists and the community development in the region area.